Digging up the Amazons?: The dangers of viewing Scythian material remains through the lens of Classical Amazon Mythopoesis - Hankinson , Elizabeth (Journal of Greek Archaeology, 2024)
In a world as heavily dominated by male heroes as Ancient Greece, the legend of the Amazons stands out in high relief. Fearsome female warriors from abroad, the Amazons conducted their lives in a manner entirely antithetical to Greek gender roles. They were skilled horsewomen, capable archers, and worthy opponents in close combat. They trained their daughters not to weave, but to fight, and not only were they uninterested in the prospect of marriage, they eschewed the society of men completely. Instead they chose to live apart in a matriarchal world of their own devising, complete with queens, generals, and fortified cities. For the Greeks, the Amazons were a paradox: objectionable in that they were barbaric foreigners, whose unnatural, belligerent and matriarchal society stood in opposition to what women ought to be, but simultaneously lauded for their beauty, athleticism, and mastery of the martial arts.